THE ROLE OF ENVIRONMENTAL FACTORS IN THE INCIDENCE AND PREVALENCE OF VECTOR-BORNE DISEASES - Hafiz Mohammed Ali Saghayir, Wael Zaylaee Shahhar, Adel Hassan Yahya Mashufi, Abdulrahman Hussain Ali Alhazmi, Faraj Muadhah Ghurm Alshehri, Obaid Saud Hassan Al-dosari, Ali Essa Ahmed Dallak, Meshari Marzouq Alhisan; Abdul Rahman Bin Muhammad Bin Abdul Rahman Bin Talha, Saud Motlaq Alotaibi, Mohammed Jaad Fahad Alotaibi, Faraj Muadhah Ghurm Alshehri, Ali Mohammed A Shrahili, Essam Essa I Mawkili, Abdullah Mubarak Abdullah Almughyirah; Mohammed Hadi Hussain Alsagoor, Talal Qaed Alotaibi, Wael Zaylaee Shahhar (Chelonian Research Foundation, 2022)
There has been much deliberation over the potential impact of climate change on the danger of vector-borne illnesses. The discussion regarding the former has centered around the extent to which the occurrence and levels of risk of vector-borne diseases are influenced by factors that are dependent on climate or factors that are independent of climate. On the other hand, the discussion regarding the latter has focused on whether changes in disease incidence are caused by climate at all, and if so, whether they can be attributed to recent climate change. In this analysis, I examine the potential impacts of climate change on illnesses transmitted by vectors, such as mosquitoes and ticks. I also explore the techniques used to forecast these impacts and provide the current data indicating increases in disease risks associated with recent climate change. Forecasts have both overestimated and underestimated the impacts of climate change. The under-estimations of consequences mostly arise from a narrow emphasis only on the direct impacts of climate on disease ecology, while disregarding the broader implications on society's ability to manage and prevent vector-borne diseases. There is growing evidence suggesting that recent climate change may have an effect on some illnesses transmitted by vectors. However, in most cases, the available data series are either too short or non-existent, and the influence of variables unrelated to climate is significant. Therefore, it is difficult to safely ascribe changes in disease risk solely to climate change. Keywords: climate change, vector-borne diseases, and public health, environmental microbiology, review.